CONTRIBUTIONS TO THE PROVISION OF BASIC SERVICES OF THE SELECTED BARANGAYS IN BAYUGAN CITY AGUSAN DEL SUR, PHILIPPINES: IT’S ADMINISTRATION AND GOVERNENCE - Marecon Comita Viray (DIA: Jurnal Administrasi Publik, 2023)
Governance has been defined as “the manner in which power is exercised in the management of the country’s economic and social resources for development”. However, governance is not simply about how government conducts business in its own sphere. It is also about how government interacts with civil society. It tells how well government has encouraged and facilitated people’s participation not only in the delivery of services but also in evaluation and monitoring of government performance itself. In spite of technological advancement in information systems, people remain the most important factor in private and public organization. None of these techniques or management methods is effective unless they are administered and carried out by competent Barangay officials. Considering the importance of human power development, The City Government of Bayugan, Agusan del Sur conducted training programs, leadership seminars, and other Seminar-Workshop to fully reach the competence of leadership for the improvement of Barangays in. Projects are being monitored every year to see and testify if one City has improved under the administration of the said officials.